Walsh’s Classroom Modes and Interactional Features of Teacher Talk in Science Class at DCS Semarang - Junior, Simon Resania; Rukmini, Dwi; Yuliasri, Issy (English Education Journal, 2021)
This research aims to find out how the realization of classroom modes and interactional features of teacher talk and identify the interactional features that either support or hindrance student's learning in science class elementary level. The descriptive qualitative method is applied in this study. Twelve lessons from 7 teachers were transcribed and analyzed using the Self Evaluation of Teacher Talk (SETT) framework adapted from Walsh (2006) supported by data interview. The findings show that all four classroom modes can be seen in all of the lessons, but classroom context modes were found in a limited portion. The teachers performed all interactional features where the most frequent occurrences are teacher echo, display question, seeking clarification, content feedback, and extended teacher turn. The lesser proportion of the interactional features are scaffolding, extended wait time, referential questions, direct repair, confirmation check, extended learner turn, teacher interruptions, form-focused feedback, and turn completion. From all the interactional features that have been employed, seeking clarification, content feedback, scaffolding, and extended wait time are strategies that potentially support students learning. On the other hand, teacher echo and display questions were found to hindrance students’ learning potentially.